Employers Perceptions of the Re-employment Barriers Faced by Older Job Hunters - Gibson, Kevin; Zerbe, Wilfred; Franken, Robert (Relations industrielles / Industrial Relations, 1993)
This study analyzed responses from 651 employers to the question: « What is the major reason why the mature unemployed so often have difficulty finding work? » Five major barriers that limit the re- employment opportunities of older job hunters were identified from employer's responses. Each of the barriers to re-employment is described in terms of the accuracy of the claim, and possible mechanisms for overcoming each barrier is discussed.